INFLUENCE OF “GADGETS DANGERS” EDUCATION ON THE LEARNING INTEREST OF ELEMENTARY SCHOOL CHILDREN IN MAKASSAR - Uchira, Uchira; Rasdin, Rasdin; Jamila Kasim (Bajang Institute, 2025)
Development of technology and information in the world has progressed very rapidly, which is marked by progress in the field of technology and information, and in Indonesia there has also been progress in this field. It is undeniable that the presence of the internet is increasingly needed in everyday life, both in socialization, education, business and so on. Social media has a big influence on a person's life, for society, adults and children are now using the internet. This study aims to determine the effect of “gadgets dangers” education on the learning interest of elementary school children in Makassar. This type of research uses a Pretest-Posttest control group design, namely a pre-experimental design with a One group pretest-posttest design approach. The population in this study were children with elementary school level totaling 55 people in Makassar. The sample size in this study used total sampling which took the entire population to be used as a sample and totaled 55 respondents in the RT Katimbang Makassar area. Data collection using questionnaires distributed before and after the intervention was given. The collected data were then processed using the Paired T-Test and Wilcoxon Test. The results obtained showed that the results of the Paired T-Test and Wilcoxon Test p = 0.000 <α = 0.05. The conclusion is that there is an influence of